Evolutionary criminology : towards a comprehensive explanation of crime - Durrant, Russil; Ward, Tony (Amsterdam : Elsevier : Academic Press, 2015)
Theories of crime typically reflect the discipline of the theorist. There has been little attempt to construct multidisciplinary frameworks that integrate psychological, biological, and sociological concepts in explaining, and controlling, criminal activity. Evolutionary behavioral science is ideally placed to provide a comprehensive and scientifically grounded framework for understanding criminal behavior. As human beings evolved, criminal behavior was a result of adaptations, or the by-products of adaptations. This book introduces a comprehensive evolutionary behavioral science approach.
Criminology and evolutionary theory -- Evolutionary theory and human evolution -- Evolutionary behavioral science -- Levels of analysis and explanations in criminology -- The evolution of altruism, cooperation, and punishment -- Distal explanations: adaptations and phylogeny -- Development -- Proximate explanations: individuals, situations, and social processes -- Social-structural and cultural explanations -- Punishment, public policy, and prevention -- The rehabilitation and reintegration of offenders -- Looking forward from the perspective of the past.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed March 19, 2015).
Keywords: Criminal anthropology; Criminology; Human evolution; Criminal behavior -- Genetic aspects; Evolution (Biology) and the social sciences; SOCIAL SCIENCE -- Criminology; Criminal anthropology; Criminal behavior -- Genetic aspects; Criminology; Evolution (Biology) and the social sciences; Human evolution; Electronic book; Electronic books; Electronic books